2018
DOI: 10.1177/0018720818784803
|View full text |Cite
|
Sign up to set email alerts
|

Using Situation Awareness and Workload to Predict Performance in Submarine Track Management: A Multilevel Approach

Abstract: Adapting automation is more likely to produce optimal outcomes if based on measurement of operator states that predict future task performance, such as workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…In one counter-intuitive finding, Loft et al (2018) found that while SAGAT was predictive of performance in a submarine management study, this was only at the between subjects level, but not at the within subjects level. This would indicate that the differences in SA between subjects correlated with performance, but not changes in an individual’s SA within a trial, which is hard to explain on any theoretical level.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In one counter-intuitive finding, Loft et al (2018) found that while SAGAT was predictive of performance in a submarine management study, this was only at the between subjects level, but not at the within subjects level. This would indicate that the differences in SA between subjects correlated with performance, but not changes in an individual’s SA within a trial, which is hard to explain on any theoretical level.…”
Section: Resultsmentioning
confidence: 98%
“…Previous research has shown that air traffic controllers do not remember aircraft call signs, for example, but rather rely on spatial memory of where air traffic is located (Endsley & Rodgers, 1998). By pinning each query to the ship contact number in the Loft et al (2018) study, rather than a spatial map as is typical with SAGAT administration, it is possible that the researchers created an artificial memory requirement that interfered with their results. This matter will require further research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, only two studies have examined the relationship between workload and performance in real-time (as opposed to aggregated at a manipulation level, such as easy vs. difficult; Loft et al, 2018;Mracek, Arsenault, Day, Hardy, & Terry, 2014). Both showed that increased workload for an individual (i.e., increased workload relative to one's own average workload) was associated with a decrease in subsequent performance (i.e., decreased performance relative to one's average performance) in command and control tasks.…”
Section: Workload and Performancementioning
confidence: 99%
“…All results we included here evaluated correlations between-participants, either averaged across participants or separate analysis of each SA-performance pairing. A handful of papers did evaluate relationships for SA-performance within-participants, but results were varied (Loft et al 2018;O'Hagan et al 2019;Strybel et al 2009). We were unable to include the small number of within-participant results because the output of multilevel models could not be converted to correlation coefficients or the results were overfit.…”
Section: Between-participants Versus Within-participantsmentioning
confidence: 99%